Meta Analysis of the Relationship between Tea Drinking Habits and the Incidence of Anemia in Pregnant Women - Samara Rahma Dania; Yulia Lanti Retno Dewi; Eti Poncorini Pamungkasari (Journal of Epidemiology and Public Health, 2022)
Background: Anemia is a nutritional problem that needs attention and is one of the public health problems in Indonesia. One of the causes of anemia in pregnant women is the consumption of tea, where tea contains polyphenols which can inhibit the absorption of iron. The purpose of this study was to analyze the available evidence related to the relationship between tea drinking habits and the incidence of anemia in pregnant women.Subjects and Method: This study uses a systematic review and meta-analysis with PICO, namely, population= pregnant women. Intervention= drinking tea. Comparison= don't drink tea. Outcome = incidence of anemia. Article searches were conducted using electronic databases such as Google Scholar and PubMed between 2013 and 2022. The keywords used were: [("drinking tea" OR "tea consumption") AND ("anemia" AND "pregnancy") OR ("pregnant" women")]. The inclusion criteria used were full paper articles with observational studies (cross-sectional), multivariate analysis with adjusted Odd Ratios (aOR) to measure the estimated effect. The article search results are listed in the PRISMA diagram and analyzed using the Review Manager 5.3 application.Results: A total of 7 articles from Ethiopia, Somalia, Nepal, and Saudi Arabia were selected to be carried out in a systematic review and meta-analysis. The data collected showed that pregnant women who had the habit of drinking tea could increase the risk of anemia 1.94 times compared to pregnant women who did not drink tea (aOR=1.94; 95% CI=1.10 to 3.43; p=0.020).Conclusion: Pregnant women who have a habit of drinking tea can increase the risk of anemia. Keywords: Pregnant women, drinking tea, and anemia Correspondence:Samara Rahma Dania. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: samaradania25@gmail.com. Mobile: +6285647233020.